FROM RIVERS TO RED BOOK: HOW CLIMATE CHANGE RESHAPES UZBEKISTAN’S ECOSYSTEMS, BIODIVERSITY, AND HUMAN WELL-BEING (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Uzbekistan sits at the climatic crossroads of Central Asia, where arid and semi-arid landscapes and heavy dependence on the Amudarya and Sirdarya rivers heighten sensitivity to warming and water scarcity. Heat extremes raise ecological and physiological stress, while hydrological shifts threaten riverine wetlands and irrigated food systems that rely on seasonal flows and groundwater recharge. Regional assessments anticipate that, by mid-century, Amudarya and Sirdarya flows could decline by roughly 5–15%, increasing the risk of water deficits across sectors [2,4].
Keywords: Climate change; biodiversity; water scarcity; Amudarya; Sirdarya; Aral Sea; tuqay; heat stress; Uzbekistan; Central Asia.